Eliminating a framing bias by using simple instructions to ‘think harder’ and respondents with managerial experience: comment on ‘breaking the frame’ - Wright, George; Goodwin, Paul (Strategic Management Journal, 2002)
Abstract This paper shows that, in terms of experimental design and ecological validity, the recent study by Hodgkinson et al. () does not ‘indicate that the framing bias is likely to be an important factor in strategic decision making.’ Nor does it suggest that ‘cognitive mapping provides an effective means of limiting the damage accruing from this bias.’ We show that the framing bias demonstrated b yHodgkinson et al. can be removed by a simpler ‘think‐harder’ manipulation with undergraduate respondents and, further, show that the bias is not present in the decisions of experienced respondents. We also demonstrate that, for experienced respondents, factors such as avoidance of risk and the creation of new strategies also characterize strategic decision making. Such components were not captured by Hodgkinson et al. 's experimental tasks. Copyright © 2002 John Wiley & Sons, Ltd.